Response on Janjua T K , et al. (J Pak Med Assoc. 74(10), 1836–1842, October 2024) Enhancing cancer care through addressing a neglected pillar: A narrative review on quality of life in Pakistani patients - Taimoor Khalid Janjua; Saniya Amir; Saad Ullah Khan; Fizza Zulfiqar; Hira Khan Afridi (Journal of the Pakistan Medical Association, 2025)
Dear Editor, I am pleased to see that our narrative review caught the attention of a medical subspecialty which can transcend the services of oncologists, surgeons, radiotherapists and ER physicians i.e. professionals under whose services/clinic any Oncology patient is most likely to end up first. Continue..